Before Westphalia: a history of international relations ante litteram - N. N. Gudalov (Vestnik MGIMO-Universiteta)
Book review: Fenenko A.V. 2022. Istoriya mezhdunarodnykh otnoshenij v dovetsfal’skuyu epokhu [History of International Relations in the Pre-Westphalian Epoch]. Moscow: Izdatelstvo “Aspekt Press”. 752 p. (in Russian)